The Characteristics of the Chemichal Properties of Ultisols Sub Groups in Some Areas of Northern Sumatra - Ewin Syahputra; Fauzi Fauzi; Razali Razali (Universitas Sumatera Utara, 2016)
The purpose of the study to determine the characteristics of the chemichal properties of ultisols sub groups in some areas of Northern Sumatra. This research uses descriptive method by conducting surveys and soil samples up to 6 sub group of Typic Hapludults, Typic Paleudults, Psammentic Paleudults, Typic Plinthudults, Typic Ochraquults, Typic Paleaquults taken a depth of 0-30 cm at random (purposive random sampling) and composited by each sub group. Parameters analyzed were soil texture, pH, C-organic, total N, total P, P-available, exch.-K, CEC, BS, Al-exch., and aluminum saturation. The results showed that soil texture in each sub group varies the sandy clay, clay, loamy sand, clay loam, clay, and sandy clay loam. Soil pH has a wry criteria except in Typic Paleudults and Typic Paleaquults is very wry. C-organic content, total N, total P, P-available, K-exch, CEC, and BS in each sub group classified in the very low to low criteria except CEC in Typic Paleudults with the criteria moderate. Ultisols sub group has the characteristic physical and chemical properties of different/ varied.Keywords : characteristic, chemical properties, ultisols sub groups, north sumatra